Las capacidades coordinativas y su influencia en la enseñanza del fútbol en los alumnos de 4º,5º y 6º año de educacion básica de la unidad educativa “Julio Serbio Ordoñez Espinoza” - Cuenca Díaz, Jayro Gustavo (2014)
The research on the theme of "coordinative abilities AND ITS INFLUENCE ON FOOTBALL TEACHING STUDENTS IN 4th, 5th and 6th YEAR BASIC EDUCATION UNIT JULIO SERBIO ORDOÑEZ ESPINOZA " aims to get to know about the coordination capacities and their influence on teaching football students 4th, 5th and 6th year of basic education Unit Serbian July Espinoza Ordonez, whose problem is: How involved coordination capacities in developing teaching football students Education Unit Serbian July Espinoza Ordonez ?; using methods Inductive Method; The Analytical Method - Synthetics. The objectives were General Purpose. Determine coordination capacities and their influence on teaching soccer students Education Unit Serbian July Espinoza Ordonez. In addition, Specific Objectives. Determine the technical fundamentals used in the development of football in the students of the Education Unit Serbian July Espinoza Ordonez. Increase the efficiency of teaching soccer to improve coordination capacities in students of the Education Unit Serbian July Espinoza Ordonez. The people with whom I was working in this research was the proposed research was conducted in the Educational Unit "Julio Serbian Ordoñez Espinoza" in the city of Loja, in the present study the sample that will work are 70 students and 2 teachers .se clear and relevant results obtained coordinative capabilities as direct and regulate movement through the central nervous system. 100% of teachers believe that the coordination capacities if they influence the teaching of football because they can develop a more coordinated and better way to soccer practice. Reaching conclusions and recommendations ending with the alternative proposal put forward.